PATHOS: Pervasive at Home Sleep Monitoring - Ian Obermiller; Sheikh I. Ahamed (International Journal of Telemedicine and Applications)
Sleeping disorders affect a large percentage of the population, and many of them go undiagnosed each year because the method of diagnosis is to stay overnight at a sleep center. Because pervasive technologies have become so prevalent and affordable, sleep monitoring is no longer confined to a permanent installation, and can therefore be brought directly into the user home. We present a unique solution to the problem of home sleep monitoring that has the possibility to take the place of and expand on the data from a sleep center. PATHOS focuses not only on analyzing patterns during the night, but also on collecting data about the subject lifestyle that is relevant and important to the diagnosis of his/her sleep. PATHOS means “evoking emotion.” Here, we mean Pathos will help us to keep healthy: both mentally and physically. Our solution uses existing technology to keep down cost and is completely wireless in order to provide portability and be easily to customize. The daytime collection also utilizes existing technology and offers a wide range of input methods to suit any type of person. We also include an in-depth look at the hardware we used to implement and the software providing user interaction. Our system is not only a viable alternative to a sleep center, it also provides functions that a static, short-term solution cannot provide, allowing for a more accurate diagnosis and treatment.